DNW: Rooksignalen uit de nieuwe wereld
A three part series about the war on terror. The documentary tries to answer to the question of who is involved in this war and how much. The main protagonist in this series is political theorist Benjamin R. Barber who is a Distinguished Senior Fellow at Demos, president and director of the international NGO CivWorld at Demos, as well as Professor of Political Science Emeritus at Rutgers University. The first part of the series entitled “The temple” focuses on Ground Zero in New York and the people affected by the collapse of the twin towers. Interviews with Tina Brown and Lisa Goldring whose great-grandfather built the World Trade Center, Manuel Castells, Professor of Sociology and Director of the Internet Interdisciplinary Institute at the Open University of Catalonia and Karen Armstrong, a British ex-nun and theologian who writes on the issue of fundamentalism. The second part called “The Mountain” focuses on the Chechen war and the guerrilla fighters, with a particular emphasis on Khozh-Ahmed Noukhaev, considered a freedom fighter by the Chechens and a terrorist by the Russians. The third part, entitled “The Challenge” debates the Washington Consensus, discusses globalization, democracy and capitalism. It focuses on the idea of ‘Open Society’ and debates the possibility of such a society in non-European nations. Interviews with CEU graduates Selima Salamova (Kazakh, UN worker), Aibek Atazin (Kazakh, juridical advisor) and Nadir Burnashev (Russian, bank director) are included here. “The Challenge” contains footage with Peter Lom, representative of the CEU Faculty, Associate Professor and PhD Director at Nationalism Studies Program, visiting Russia and talking about CEU, George Soros and the idea of Open Society. This third part of the series contains interviews with Javier Solana (Secretary General of EU between 1999 and 2009), Erkki Sakari Tuomioja (former Minister for Foreign Affairs of Finland between 2000 and 2007), Ulrich Beck (German sociologist, professor at Munich University and at the London School of Economics), Mary Kaldor (British Professor of Global Governance at the London School of Economics and the Director of its Centre for the Study of Global Governance), Narcís Serra i Serra (former Mayor of Barcelona, former Minister of Defence of the Government of Spain, former Vice President of the Spanish Government), George Soros (financier, philanthropist and Founder of the CEU) and Yehuda Elkana (President and Rector of the CEU).